2008
DOI: 10.1107/s0021889808017883
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of dynamical diffraction focusing by a bent crystal wedge in Laue geometry

Abstract: Recent X‐ray optical experiments have validated previous theoretical work on focusing by bent crystals in Laue geometry. It was shown that a suitable choice of the crystal thickness significantly improves the focusing performance of the crystal by combining the dynamical focusing of the Borrmann triangle with the geometrical focusing obtained by the crystal bending. The best focus size achieved during the experiments was less than 5 µm and is in practice limited by the source demagnification for the considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Mocella et al (2004Mocella et al ( , 2008 The polychromatic focusing condition (1) can be expressed as R cos B ¼ 2pq=ðp À qÞ, which implies p e ¼ q e ¼ 2pq=ðp þ qÞ. Mocella et al (2004Mocella et al ( , 2008 The polychromatic focusing condition (1) can be expressed as R cos B ¼ 2pq=ðp À qÞ, which implies p e ¼ q e ¼ 2pq=ðp þ qÞ.…”
Section: Distant Point Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…Mocella et al (2004Mocella et al ( , 2008 The polychromatic focusing condition (1) can be expressed as R cos B ¼ 2pq=ðp À qÞ, which implies p e ¼ q e ¼ 2pq=ðp þ qÞ. Mocella et al (2004Mocella et al ( , 2008 The polychromatic focusing condition (1) can be expressed as R cos B ¼ 2pq=ðp À qÞ, which implies p e ¼ q e ¼ 2pq=ðp þ qÞ.…”
Section: Distant Point Sourcementioning
confidence: 99%
“…In the approach of Mocella et al (2004Mocella et al ( , 2008, the illumination on the crystal entrance surface is considered to be incoherent, as a consequence of polychromaticity. There would therefore be no influence of the source-to-crystal distance on the dynamical focusing behaviour.…”
Section: Coincidence Of Dynamical and Polychromatic Focusing And Compmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the focusing performance can indeed be strongly improved by weak asymmetry, as compared to the case of symmetric geometry. We intend to continue the present analysis by considering the important case of a polychromatic source instead of the monochromatic source considered in the present work; for this purpose, it will be necessary to combine the present analysis with the condition for polychromatic focusing which is cos 2 =q À cos 1 =q ¼ 2=R (Chukhovskii & Krisch, 1992;Mocella et al, 2004Mocella et al, , 2008Guigay et al, 2013) and to discuss the influence of the dependence on the X-ray energy of the lateral displacement x c pointed out in the present investigation. In the case of a symmetric reflection, according to equation (34) with s ¼ 0, x c ' Àðt sin B Þ=2, if q and R cos B are much smaller than p; the lateral displacement is consequently approximately proportional to the X-ray energy.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 97%
“…It was experimentally confirmed by Aristov et al (1978Aristov et al ( , 1980Aristov et al ( , 1982, and by Koz'mik & Mikhailyuk (1978). Recently the effect of focusing in bent-crystal systems was considered theoretically by Mocella et al (2004Mocella et al ( , 2008, and by Nesterets & Wilkins (2008) as a way for improving polychromatic focusing.…”
Section: Figurementioning
confidence: 99%